Commentary on C. Trevor & D. Huron Are Humoresques Humorous? On the Similarity Between Laughter and Staccato - M, J (Empirical Musicology Review, 2019)
This commentary discusses and comments on the study by Trevor and Huron on the acoustical similarities between human laughter and staccato articulation in music.